Investigating Advertising Strategies: A Critical Discourse Analysis of Social Media Advertisements in Pakistan - Shah, Muhammad Mubeen; Islam, Muhammad (Annals of Human and Social Sciences, 2024)
This study aims to analyze advertising strategies on social media and customer feedback towards those ads, focusing on trends across various platforms. Drawing from Van Dijk’s (1999) model of language control and Kress and Leeuwen’s (2020) multimodal framework, this research explores how advertisers influence consumer behavior through linguistic and visual elements. Qualitative analysis was conducted on advertisements from randomly selected Facebook brand pages. Both textual and image analyses were applied to examine how these ads persuade consumers. The analysis revealed that advertisers use specific linguistic choices and images to shape consumer perceptions. Moreover, advertisers frame a lifestyle necessary for society to live a better life, and the pictures of celebrities or products have a greater space than the text itself that forces the consumers to take immediate decision. Customers, in turn, engage by showing interest and asking questions in the comment sections. Future studies could use this research to raise awareness of how social media advertising influences consumer behavior and encourage more informed interactions with such advertisements.